The information in the internet about study programmes that are provided in Lithuanian higher education institutions via information and communication technologies - Stonkienė, Marija (Information & Media, 2015)
This article presents the research on the information in the internet about the study programmes that are provided in Lithuanian higher education institutions via information and communication technologies. This research presents an analysis of e-learning opportunities in 2014 that are available in the Open Information Consultation and Orientation (AIKOS) system, the Lithuanian Higher Education Association Admission (LAMA BPO) websites, and the websites of higher education institutions that have e-learning offerings.The conducted research drew attention to the inadequate, unsystematic and incompatible provision of information on e-learning programmes that are available in higher education institutions on the nation-wide level. Higher education institution website analysis has revealed different levels of access to information to prospective students (from the complete lack of information to particularly detailed information). The results of the research have also shown the nation-wide need of solutions on distance education methods that implement information and communication technologies.